An outcomes research perspective on medical education: Has anything changed in the last 18 years?. (2nd December 2022) - Emery, Matt; Wolff, Margaret; Merritt, Chris; Ellinas, Herodotos; McHugh, Douglas; Zaher, Mohammad; Semiao, Meghan L.; Gruppen, Larry D.
Abstract: Purpose: Medical education research focused on patient-centered outcomes holds the promise of improved decision-making by medical educators. In 2001, Prystowsky and Bordage demonstrated that patient-centered outcomes were evaluated in fewer than one percent of studies published in a survey of major medical education journals. Though many have called for increased inclusion of patient-centered outcomes in medical education literature, it remains uncertain to what degree this need has been addressed systematically. Methods: Using the same data sources as in the original report (Academic Medicine, Medical Education, and Teaching and Learning in Medicine), we sought to replicate Prystowsky and Bordage's study. We extracted data from original empirical research reports from these three journal sources for the years 2014–2016. We selected 652 articles that met the inclusion criteria for further analysis. Results: Study participants were largely trainees (64% of studies) or faculty (25% of studies). Only 2% of studies included patients as active or passive participants. Study outcomes reported were satisfaction (40% of studies), performance (39%), professionalism (20%), and cost (1%). Conclusions: These results do not differ significantly from the original 2001 study. The medical education literature as represented in these three prominent journals has made little progress in placing a greater focus on patient-centered outcomes.